Conciliation and mediation in civil and Islamic family laws: issues and challenges - Abdul Hak, Nora (2011)
Introduction In UK, Mediation is introduced under the new law as a result of dissatisfaction with the procedural aspects of the law and ineffectiveness of the provisions intended to encourage reconciliation. The same also happen in Malaysia however, there has been no changes have taken place. Mediation has two main objects that are to define the matters on which the parties are in dispute and to encourage them to come to an agreed solution. The growth of interest in mediation reflects the changed attitude towards financial consequences and especially its effect on the children of the marriage. Research suggests that the children find emotional adjustment more difficult if the parents’ relationship is hostile and conflict between them continues after divorce or separation, particularly if contact with one parent is not maintained. One of the strongest arguments in favour of mediation is that the possibility of bitterness will be reduced and the prospects of both spouses continuing to play an active role as parents will be enhanced if they can reach agreement. Mediation enables the parties to retain control of their own affairs rather than have solution imposed on them.